N-domain of human adhesion/growth-regulatory galectin-9: Preference for distinct conformers and non-sialylated N-glycans and detection of ligand-induced structural changes in crystal and solution - Solís, Dolores; Maté, María Jesus; Lohr, Michaela; Ribeiro, João P.; López-Merino, Lara; André, Sabine; Buzamet, Eliza; Javier Cañada, F.; Kaltner, Herbert; Lensch, Martin; Ruiz, Federico M.; Haroske, Gunter; et al. (International journal of biochemistry & cell biology, 2010)
Human tandem-repeat-type galectin-9 is a potent adhesion/growth-regulatory effector via lectin capacity of its N- and C-terminal domains. This bioactivity prompted further crystallographic study of the N-domain, combined with analysis in solution. Binding of lactose markedly increased the N-domain's resistance to thermal denaturation. Crystallography revealed its intimate contact profile, besides detecting an extension of the β-sandwich fold by an antiparallel β-strand F0 aligned to the C-terminal F1 strand. Ligand accommodation in its low-energy conformation leads to a movement of Arg87's side chain. As consequence, the ligand's glucose moiety and Arg87 become hydrogen bonded. The resulting predictions for spatial parameters in solution were verified by determining (a) the pattern of magnetization transfer from the protein to protons of lactose and Forssman disaccharide by NMR spectroscopy and (b) the ellipticity changes at wavelengths characteristic for Trp/Tyr residues in near-UV CD spectroscopy. Whereas solid-phase assays confirmed a previously noted tendency for homo- and heterotypic aggregation, gel filtration and ultracentrifugation disclosed monomeric status in solution, in line with crystallographic data. Using cell mutants with defects in glycosylation, this lectin domain was shown to preferentially bind N-glycans without α2,3-sialylation. Since proximal promoter sequences were delineated to diverge markedly among galectin genes and resulting differences in expression profiles were exemplarily documented immunohistochemically, the intrafamily diversification appears to have assigned this protein to a characteristic expression and activity profile among galectins. Our data thus take the crystallographic information to the level of the lectin in solution and in tissues by a strategic combination of spectroscopic and cell/histochemical assays.
Gesehen am 11.08.2023